An analysis of anxiety levels among volleyball athletes during a provincial inter-club tournament in Jakarta, Indonesia - Raga, Rea Rizkita; Lasma, Yunita (Physical Education and Sports: Studies and Research, 2025)
Background: Competitive anxiety is a key psychological factor that can significantly affect an athlete's performance. In volleyball, high-pressure situations often lead to anxiety, potentially hindering players' ability to perform optimally. Objectives: This study aims to assess the levels of anxiety experienced by volleyball athletes competing in the Special Capital Region Jakarta Inter-Club Provincial Championship. Methods: A descriptive quantitative design was used, with data collected through a survey involving 70 volleyball athletes. The instrument used was a 35-item anxiety questionnaire categorized into two phases: before the match (18 items) and during the match (17 items). Responses were measured using a 5-point Likert scale. Validity testing confirmed all items were valid, and the instrument showed high reliability (α = 0.954), as analyzed using SPSS 23. Results: During the match, 35.7% of athletes experienced high anxiety, while 64.3% showed low anxiety. Prior to the match, 44.3% reported high anxiety and 55.7% reported low anxiety. Overall, 36.6% of athletes showed high anxiety levels, while 61.4% displayed low levels. These results indicate that most athletes have relatively good emotional regulation abilities in competitive situations. Conclusions: The study underscores the critical role of psychological readiness in athletic performance. Coaches and policymakers are encouraged to integrate structured mental training programs into athlete development. Future research should explore variables contributing to anxiety, such as playing position, competitive experience, and demographic factors like age and gender.